Gender Differences in Outpatient Pediatric Drug Utilization: A Cohort Study From Southern Italy - Ferrajolo, Carmen; Sultana, Janet; Ientile, Valentina; Scavone, Cristina; Scondotto, Giulia; Tari, Michele; Trifirò, Gianluca; Rossi, Francesco; Capuano, Annalisa (Frontiers in Pharmacology, 2019)
Objective: The aim of this retrospective population-based cohort study is to in-depth investigate gender-specific drug utilization pattern in pediatric outpatient population. Methods: By using a large administrative database of the Local Health Unit of Caserta (Southern Italy), a pediatric cohort from the birth to 18 years was observed over 6 years (from 1st January 2010 to 31st December 2015). Yearly prevalence of drug use per 100 inhabitants as well as the median number of prescriptions was stratifying by gender. Prevalence of acute and recurrent use of the most frequently used active substances was calculated for the year 2015. Results: A decreasing trend in prevalence of drug use (−3.2%, with a reduction of median number of drugs dispensed) was observed in children for both sexes, from 2010 to 2015. In 2015, the drug classes most commonly used among children of any age were modestly but consistently prescribed more to males than to females: systemic anti-infective drugs (M = 43.5%; F = 42.3%), respiratory tract drugs (M = 29.0%; F = 26.1%), and hormones (M = 13.1%; F = 11.3%). Irrespective of gender, beclomethasone was the most utilized active substance in the first 2 years of life, while thereafter amoxicillin/clavulanate in combination. Conclusions: In a large population of pediatric outpatients no major difference was seen between genders, although commonly used drug classes; in particular, antibiotics, respiratory tract drugs and Hormones with corticosteroids for systemic use prescribed modestly but consistently to larger extent in males than females.